A Case of Penetrating Injury from the Oropharynx to the Posterior Neck in an Elderly Patient Who Underwent Toothbrush Extraction with Angiography - HIGA, Tsutomu; HIGA, Moritoshi; SAWADA, Shigeki; KANO, Takeshi; YAMAMOTO, Masashi; YAMASHIRO, Kie; ARAKAKI, Keiichi; UEDA, Gosei; NAKASONE, Yasunari; TATETSU, Masaharu; NAKAMA, Joji (Journal of the Japanese Society of Oral and Maxillofacial Traumatology, 2023)
Toothbrush trauma is reported to be more common in children, and it has been pointed out that such trauma can lead to fatal complications even when the local findings are minor. We report the case of an elderly patient with a deep injury from the oral cavity to the posterior neck area caused by a toothbrush. The patient, a 90-year-old woman, fell with a toothbrush in her mouth and sustained an injury, and was brought to our emergency room. The tip of the toothbrush reached the lower mastoid process and was removed under general anesthesia. Two weeks after surgery, a finding of suspected abscess formation was observed in the parapharyngeal space. Three weeks after surgery, the clinical findings improved and the patient was discharged. Even if the local findings are not so severe, it is important to follow the patient carefully under inpatient care based on a comprehensive evaluation of imaging and blood sampling.